2017
DOI: 10.1038/s41598-017-10675-6
|View full text |Cite|
|
Sign up to set email alerts
|

Toxoplasma Modulates Signature Pathways of Human Epilepsy, Neurodegeneration & Cancer

Abstract: One third of humans are infected lifelong with the brain-dwelling, protozoan parasite, Toxoplasma gondii. Approximately fifteen million of these have congenital toxoplasmosis. Although neurobehavioral disease is associated with seropositivity, causality is unproven. To better understand what this parasite does to human brains, we performed a comprehensive systems analysis of the infected brain: We identified susceptibility genes for congenital toxoplasmosis in our cohort of infected humans and found these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 192 publications
(225 reference statements)
2
75
0
1
Order By: Relevance
“…Despite this caveat, our study provides proof of principle that chronic latent toxoplasmosis in HD mice potentiates established markers of HD progression. Interestingly, a recent study reported that early--life infection with T. gondii alters a wide array of human genes and pathways implicated in the pathogenesis of neurological disorders including HD, Alzheimer's disease, and seizure disorders [61]. In humans, the prevalence of T. gondii increases with age [6,62].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this caveat, our study provides proof of principle that chronic latent toxoplasmosis in HD mice potentiates established markers of HD progression. Interestingly, a recent study reported that early--life infection with T. gondii alters a wide array of human genes and pathways implicated in the pathogenesis of neurological disorders including HD, Alzheimer's disease, and seizure disorders [61]. In humans, the prevalence of T. gondii increases with age [6,62].…”
Section: Discussionmentioning
confidence: 99%
“…This might not have been identified in transcriptomic studies published of whole infected brain tissue, which principally identified changes in expression of host immune response genes with the mixture of cell types in the brain (27,28). A recent transcriptomic study by Ngô et al (73) identified differentially expressed genes after only 18 h of infection (i.e., during vegetative replication stages) in neural stem cells that expressed a range of markers for structural proteins found among different types of neurons and astrocytes. Hence, those results are difficult to compare with our approach using neuronal cells that are fully functional in synthesis and release (with potassium activation) of DA and NE to investigate changes in expression of neuronal genes.…”
Section: Downregulation Of a Key Enzyme For Norepinephrine Synthesis mentioning
confidence: 99%
“…Toxoplasma gondii infection can cause miscarriage when women are first exposed during pregnancy, severe ocular and neurological lesions in newborns and systemic disease and deaths in immunocompromised individuals (Maenz et al, ; Sukthana, ; Torgerson & Mastroiacovo, ). Infection has also been associated with schizophrenia and neurodegenerative diseases in congenitally infected people (Brown et al, ; Ngô et al, ). Although less common, severe health outcomes in immunocompetent individuals following acquired infection with certain strains of T. gondii have also been reported and include ocular toxoplasmosis, pneumonia, organ failure and death (Carme, Demar, Ajzenberg, & Dardé, ; Cortés & Aguirre, ; Glasner et al, ; Leal et al, ).…”
Section: Introductionmentioning
confidence: 99%